Clinical and MRI predictors of response to interferon‐beta and glatiramer acetate in relapsing–remitting multiple sclerosis patients. Issue 7 (20th February 2013) - Romeo, M.; Martinelli‐Boneschi, F.; Rodegher, M.; Esposito, F.; Martinelli, V.; Comi, G.; ,
<x xml:space="preserve">Abstract</x> Background and purpose It is still unclear which patients benefit more from available disease‐modifying treatments (DMTs) in multiple sclerosis (MS). Our objective is to identify the baseline clinical and magnetic resonance imaging (MRI) predictors of response to first‐line DMTs in a cohort of relapsing–remitting (RR) MS patients in a real‐world clinical setting. Methods Consecutive naïve RRMS patients treated with interferon‐beta or glatiramer acetate have been included and followed for 2 years. Patients were grouped into responders (R) in case of absence of clinical and MRI activity, and non‐responders (NR) if the on‐treatment annualized relapse rate (ARR) reduction was < 50% of the ARR in the 2 years before treatment or in the presence of MRI activity (≥ 2 active lesions at 1‐year MRI or ≥ 4 active lesions at 1 + 2‐year MRI). Results At 2‐year follow‐up, 272 patients were R (34.6%) and 322 NR (40.9%), and multivariate analysis revealed that a later age at onset of the disease (P < 0.0001), a lower disability (P < 0.0001) and a lower number of gadolinium‐enhancing lesions at baseline MRI (P = 0.002) were predictors of efficacy of DMTs. Moreover, the first year response had a good predictive power on the second year, as 73.7% of 1‐year R had no evidence of clinical and MRI activity within the ensuing year. Conclusion A lower baseline MRI and clinical activity have been identified as predictors of DMT efficacy in patients with RRMS in routine clinical practice. Evaluation of clinical and MRI activity at 1 year is recommended to monitor patients over time.